Zinc-doped BSCF perovskite membranes for oxygen separation - Zhang, X.; Motuzas, J.; Liu, Shaomin; Diniz da Costa, J. (Pergamon Press, 2017)
This work investigates the partial substitution of Zn in the B-site of perovskite as Ba 0.5 Sr 0.5 (Co 0.8 Fe 0.2 ) 1- x Zn x O 3- d . The membranes were tested for oxygen separation from air and Zn incorporation into the BSCFZ cubic crystal structure proved to be effective as oxygen fluxes increased as compared with a pure BSCF (x = 0, no Zn). This was attribute to the increase in oxygen vacancy concentration as a function of Zn concentration. As a result, oxygen fluxes for the BSCFZ membranes were 200% (700 °C) and 32% (900 °C) higher than the BSCF analogue membrane. However, the correlation between oxygen vacancy concentration and oxygen flux diverged for Zn concentrations x = 0.08, which was associated with the shift and broadening of the main XRD peak 2? = 31.81° of the BSCFZ cubic structure caused by an additional oxide phase (ZnO). Zn doping also affected the microstructure of the sintered BSCFZ membranes. Grain boundary dimensions reduced as Zn substitution in the B-site increased to x = 0.06 up to 800 °C, resulting in improved oxygen fluxes. Contrary to this, high Zn concentration x = 0.08 increased grain boundary and reduced oxygen fluxes. Therefore, the Zn solubility into BSCF impact upon the oxygen vacancy and microstructural formation, which in turn affected the transport of oxygen ions through the membrane.